Karakteristik Peternak dan Tingkat Masukan Teknologi Peternakan Sapi Potong di Lembah Prafi Kabupaten Manokwari : Farmer Characteristic and Level of Technology Inputs of Beef Husbandry at Prafi Valley, Regency of Manokwari - Agustinus Gatot Murwanto (Fakultas Peternakan Universitas Papua, 2008)
A study was carried out to determined farmer characteristics and level of technology inputs for beef husbandry at Prafi Valley, Manokwari Regency. This study was conducted at three districts: Warmare, Prafi, and Masni. Stratification technic was applied base on farmer tribes (Java, Flores and Arfak). Eighty nine (89) farmers were involved in this study: Java tribe: 39 farmers, Folres and Arfak tribes: 25 farmer each. Data collection was done through a structured interview based on questioner. Statistic description technic, Mann Whitney Test, Kruskal Wallis Test, and Spearman Correlation were adopted for data analysis. Result of the study showed a high variation among tribes in level of beef farmer characteristies: age, education level, husbandry experience, and cattle ownership, at Prafi Valley. Tribe or etnic backgrounds were significantly influenced the technology level inputs for husbandry. Farmer characteristics had no correlation with the level of technology inputs for beef husbandry. The level of technologi inputs at Prafi Valley mostly low to average. The best inputs technology was found among Java tribe farmers.